Photo‐biocatalytic One‐Pot Cascades for the Enantioselective Synthesis of 1, 3‐Mercaptoalkanol Volatile Sulfur Compounds. (14th April 2018) - Lauder, Kate; Toscani, Anita; Qi, Yuyin; Lim, Jesmine; Charnock, Simon J.; Korah, Krupa; Castagnolo, Daniele
Abstract: The synthesis of enantiomerically pure 1, 3‐mercaptoalkanol volatile sulfur compounds through a one‐pot photo‐biocatalytic cascade reaction is described. Two new KRED biocatalysts with opposite enantioselectivity were discovered and proved to be efficient on a wide range of substrates. The one‐pot cascade reaction combining photocatalytic thio‐Michael addition with biocatalytic ketoreduction in an aqueous medium provides a green and sustainable approach to enantiomerically pure 1, 3‐mercaptoalkanols in high yields with excellent enantioselectivity.